Effect of weed management practices on yield and economics of wheat (Triticum aestivum L.) - Utkarsh Singh,; Anil Kumar Singh,; Sudhir Kumar Rajpoot,; Tejbal Singh,; Ashish Kumar Verma, (Annals of Agricultural Research, 2023)
A field experiment was conducted at Agronomy research farm of Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya (U.P.) during rabi season of 2020-21 to determine the most effective herbicide and herbicide combinations for controlling the Phalaris minor and other weeds in wheat crop. The results revealed that post emergence spray of ready mixture of sulfosulfuron + metsulfuron @ 30 g + 2g a.i. ha-1 recorded significantly the lowest weed population of Phalaris minor and other weeds and dry weight of weeds at all stages of crop growth (except 30 days of crop growth) as compared to rest of the treatments. However, weedy check recorded the highest reduction in grain yield i.e. 30.22%. Among the weed management treatments lowest reduction in grain yield was recorded with post emergence spray of ready mixture of sulfosulfuron + metsulfuron @ 30g + 2g a.i. ha-1 i.e. 3.41%. Weed free up to 60 days recorded significantly highest grain yield of 42.05 q ha-1 followed by sulfosulfuron + metsulfuron @ 30 g + 2g a.i. ha-1 with 40.66 q ha-1. In terms of economics, net return and benefit-cost ratiowere found maximum with sulfosulfuron + metsulfuron @ 30 g + 2g a.i. ha-1 followed by clodinofop + metsulfuron @ 60 + 4g a.i. ha-1 whereas, weedy plots had lowest net return and benefit cost ratio as compared to other weed control treatments.